Brassica carinata: Biology and agronomy as a biofuel crop. Issue 4 (17th February 2021) - Seepaul, Ramdeo; Kumar, Shivendra; Iboyi, Joseph E.; Bashyal, Mahesh; Stansly, Theodor L.; Bennett, Rick; Boote, Kenneth J.; Mulvaney, Michael J.; Small, Ian M.; George, Sheeja; Wright, David L.
Abstract: The environmental consequences of using nonrenewable fossil fuels have motivated a global quest for sustainable alternatives from renewable sources. Carinata has been developed as a low carbon intensity, non‐food oilseed biomolecular platform to produce advanced drop‐in renewable fuels, meal, and co‐products. The crop is widely adaptable to grow in the humid subtropical and humid continental climatic regions of Asia, Africa, North America, South America, Europe, and Australia as a spring or winter crop. Carinata is heat tolerant, resistant to diseases and seed shattering with lower water‐use requirements than other oilseed brassicas. Adopting carinata in double‐cropping systems would require continuing research to integrate crop biology with agronomy, to understand growth and development and its interaction with agricultural inputs and management. Site‐specific best management agronomic practices and crop improvement research to develop frost‐tolerant, early‐maturing, nutrient use‐efficient, and high yielding varieties with desirable oil content and fatty acid profile will enhance the crop's adaptability and economic viability. The exploitation of intra‐ and interspecific and intra‐ and intergeneric diversity will further enhance carinata productivity and resistance to biotic and abiotic stresses. This review attempts to present a comprehensive description of carinata's biology, beginning with its origin and current state of distribution, availability of genetic and genomic resources, and a discussion of its morphology, phenology, and reproduction. A detailed analysis of the agronomy of the crop, including planting and germination and management practices, is presented in the context of crop growth and development. This will facilitate global adoption, sustainable production, and commercialization of carinata as a dedicated biofuel oilseed crop in diverse cropping systems and growing regions of the world, including the Southeast United States. Abstract : Brassica carinata is a low carbon intensity, non‐food oilseed biomolecular platform being researched to produce advanced drop‐in renewable fuels, meal, and co‐products. Successful commercial production of carinata requires continued research to integrate the crop's biology with its agronomy, to understand growth and development and its interaction with agricultural inputs and management. Specifically, site‐specific best management agronomic practices and crop improvement research to develop frost‐tolerant, early‐maturing, nutrient use‐efficient, and high yielding varieties with desirable oil content and fatty acid profile will enhance the crop's adaptability and economic viability across diverse double‐cropped farming systems.